Wooden crosses a film by Raymond Bernard = Les croix de bois - Dorgelès, Roland 1885-1973 (The Criterion coll., 2007)
Film adaptation of an anti-war novel that follows a French regiment in World War I as it trudges from patriotism to disillusionment.
Orig.: F 1932. - S/W
Keywords: Dorgelès, Roland <1886-1973> - Adaptations - Drama; Dorgelès, Roland <1886-1973> -- Film and video adaptations; Soldiers - France - Drama; World War, 1914-1918 - France - Drama; Weltkrieg (1914-1918); Soldiers -- France -- Drama; World War, 1914-1918 -- France -- Drama; France - Drama; Frankreich; France -- Drama; Anti-war films; Feature films; Film adaptations; Foreign films - France; Adaptation - Feature; War - Feature; War films